Effectiveness of an intercritical heat-treatment on localized corrosion resistance at the microstructural boundaries of medium-carbon steels. (1st July 2019) - Kadowaki, Mariko; Muto, Izumi; Katayama, Hideki; Masuda, Hiroyuki; Sugawara, Yu; Hara, Nobuyoshi
Highlights: Localized corrosion was initiated at the pearlite colony boundaries and prior austenite grain boundaries in AISI 1045 steels. Phosphorus segregation was detected at these boundaries. The localized corrosion resistance at these boundaries was improved by an intercritical heat-treatment. Abstract: The localized corrosion resistance at the microstructural boundaries of AISI 1045 carbon steels was accessed. Under KFM measurements, regions with low corrosion potentials were found at the pearlite colony boundary in the ferrite-pearlite structure and the prior austenite grain boundary in the martensite structure, and phosphorus was segregated in these regions. The localized corrosion resistance at these boundaries was improved via intercritical heat-treatment at 1023 K (the two-phase region of austenite and ferrite) after austenitizing, which may be attributable to the apparently homogenous dissolution of ferrite forming elements, such as phosphorus, in the ferrite phase during the treatment.